2016
DOI: 10.1002/ange.201602907
|View full text |Cite
|
Sign up to set email alerts
|

Minimization of Surface Energies and Ripening Outcompete Template Effects in the Surface Growth of Metal–Organic Frameworks

Abstract: As well-oriented, surface-bound metal-organic frameworks become the centerpiece of many new applications, ap rofound understanding of their growth mode becomes necessary.This work shows that the currently favored model of surface templating is in fact as pecial case valid only for systems with am ore or less cubic crystal shape,w hile in less symmetric systems crystal ripening and minimization of surface energies dominate the growth process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 44 publications
(83 reference statements)
1
3
0
Order By: Relevance
“…The adsorption capacity and dynamics of the other three SURMOFs are somewhere in between those of SURMOF-A and SURMOF-B. As reported previously, 32 the orientation of the SURMOFs does not play a significant role for adsorption capacity and dynamic rate of individual SURMOFs, as these values are rather dominated by the accessible pore volume and hindrance of appended functional groups than by the direction of pore opening, as can be seen for the most disordered SURMOF-E. Interestingly, for the 10 investigated MTV-SURMOFs, except for SURMOF-AB and SURMOF-BE, which show lower benzene adsorption capacitance than SURMOF-B, all other SURMOFs display a significantly higher benzene adsorption capacity (Figures S49−S52). For example, the maximum adsorption capacity of 97 mg g −1 for SURMOF-BCD is reached within 10 min, which is 1.7 times higher than for SURMOF-B, and 2.6 times higher than for the average of SURMOF-A to E (38 mg g −1 , calculated from Figure 6a).…”
Section: ■ Introductionsupporting
confidence: 75%
See 2 more Smart Citations
“…The adsorption capacity and dynamics of the other three SURMOFs are somewhere in between those of SURMOF-A and SURMOF-B. As reported previously, 32 the orientation of the SURMOFs does not play a significant role for adsorption capacity and dynamic rate of individual SURMOFs, as these values are rather dominated by the accessible pore volume and hindrance of appended functional groups than by the direction of pore opening, as can be seen for the most disordered SURMOF-E. Interestingly, for the 10 investigated MTV-SURMOFs, except for SURMOF-AB and SURMOF-BE, which show lower benzene adsorption capacitance than SURMOF-B, all other SURMOFs display a significantly higher benzene adsorption capacity (Figures S49−S52). For example, the maximum adsorption capacity of 97 mg g −1 for SURMOF-BCD is reached within 10 min, which is 1.7 times higher than for SURMOF-B, and 2.6 times higher than for the average of SURMOF-A to E (38 mg g −1 , calculated from Figure 6a).…”
Section: ■ Introductionsupporting
confidence: 75%
“…This result hinted toward the fact that, besides the pK a effect, crystal growth dynamics (e.g., ripening or flipping of SBUs) might be also involved in controlling the crystal orientation of SURMOFs as reported previously. 25,32 SEM images revealed that SURMOF-A 0.8 D 0.2 and SURMOF-A 0.5 D 0.5 consisted of squarelike nanoplates (Figure 3e,f), similar to SURMOF-A. In the case of SURMOF-A 0.2 D 0.8 , nanorods with somewhat tilted orientation (likely responsible for the misorientation seen in the spectra) were observed (Figure 3g).…”
Section: ■ Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…In a subsequent study on an orthorhombic [Cu 2 (sdb) 2 (bipy)] MOF, Yu et al again used IRRAS and SXRD to determine how surface area minimization and Ostwald ripening could out compete templating effects in the oriented growth of the MOF with either PPP1 or MTCA functionalized surfaces. 159 As measured by IRRAS data taken after one deposition cycle, and in contrast with the Cu 2 -paddlewheel results, both PPP1 and MTCA displayed the same orientational preference, indicating that the SAM surface chemistry did not play a large role in determining crystal orientation for the [Cu 2 (sdb) 2 (bipy)] system. Instead, their results supported the important role of surface energy minimization and Ostwald ripening over templating effects (at least of less symmetric crystals) on MOF thin-film growth.…”
Section: Irrasmentioning
confidence: 99%